Comparison of atmospheric deposition of copper, nickel, cobalt, zinc, and cadmium recorded by finnish peat cores with monitoring data and emission records - Rausch, Nicole; Nieminen, Tiina; Ukonmaanaho, Liisa; Le Roux, Gaël; Krachler, Michael; Cheburkin, Andriy K.; Bonani, Georges; Shotyk, William (Environmental science & technology, 2005)
This study aims to determine the extent to which the accumulation rates of Cu, Ni, Co, Zn, and Cd in peat cores agree with established histories of atmospheric emission from local point sources. Metals accumulating in three Finnish peat cores with known metal deposition histories have been measured using inductively coupled plasma-sector field mass spectrometry. Samples were age-dated using both 210Pb and 14C (bomb pulse curve). At the Outokumpu (OUT) site as well as the low-background site Hietajärvi (HIJ), 210Pb age dates are in excellent agreement with the 14C bomb pulse curve method results, and the precision is between 1 and 10 years for most of the samples; at the Harjavalta (HAR) site, precision is >6 years. Mean regional “background” concentrations have been calculated from deeper peat layers of the HIJ site (μg g-1):  Cu, 1.3 ± 0.2 (n = 62); Co, 0.25 ± 0.04 (n = 71); Cd, 0.08 ± 0.01 (n = 23); and Zn, 4 ± 2 (n = 40). For layers accumulated within the past 100 years, accumulation rates (ARs) have been calculated. At sites with <0.06 g m-2 cumulative Ni inventory (HIJ and OUT), ARs of Cu and Co trace the known metal deposition histories very well. At HAR, where metal inventories are much greater, Cu and Co are mobile. ARs of Zn were between 3 and 30 mg m-2 year-1 and those of Cd between 24 and 140 μg m-2 year-1 at all sites and are independent of the chronology of their inputs from the atmosphere.
Gesehen am 29.09.2020